The canine connection II: dogs and southern African herders - Mitchell, P. (Southern African Humanities, 2014)
Dogs were one of several domestic animals kept by precolonial southern African herders, but their economic and social relevance for these communities has been little explored. This paper reviews the evidence for the dog’s introduction into southern Africa and assesses the relative strengths of various lines of evidence (osteology; ancient DNA; animal tracks; faunal taphonomy) to identify those instances where the presence of dogs can most convincingly be established on probable herder sites. How herders used dogs is discussed next, along with the more limited ethnographic and historical evidence for their social and symbolic associations. It seems likely that the principal function of dogs for precolonial herders was as an alarm and deterrent against predators that might attempt to seize their livestock. The possibility that dogs dispersed into southern Africa as part of a package with sheep and cattle therefore merits further investigation.